Single cell RNA-seq reveals the CCL5/SDC1 receptor-ligand interaction between T cells and tumor cells in pancreatic cancer. (1st October 2022) - Chen, Kai; Wang, Yazhou; Hou, Yuting; Wang, Qi; Long, Di; Liu, Xinxin; Tian, Xiaodong; Yang, Yinmo
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by the complex tumor microenvironment (TME), consisting of an abundance of stromal cells. Among them, tumor infiltrating T cells play a pivotal role in tumor progress. To identify the full spectrum and developmental trajectory of T cells and their crosstalk with tumor cells in PDAC, we conducted scRNA-seq analysis based on multiple datasets from our institution and open databases. We delineated the cellular landscape and transcriptional dynamics of T cells in PDAC. Through the inferCNV analysis and known tumor markers, the malignant ductal cells were identified. The inter-patients heterogeneity of tumor cells was also identified. After integrating T cells and malignant ductal cells, we found the CCL5-SDC1/4 receptor-ligand interactions between them. Furthermore, we demonstrated that CCL5 promoted tumor cells migration via interacting with SDC1 in vitro. Our findings pave the way for characterizing the heterogeneity and development trajectory of T cells, and cell-to-cell communications in TME of PDAC, which might provide a new target for immunotherapy. Highlights: We delineated the cellular landscape and transcriptional dynamics of T cells in PDAC. The malignant ductal cells in PDAC were identified through the inferCNV analysis and known tumor markers. We found the CCL5-SDC1/4 receptor-ligand interactions between T cells and tumor cells. CCL5 could promote tumor cells migration via interacting with SDC1.